Effect of Gd substitution on the dielectric and magnetic properties of BSFO-based multiferroic system - Verma P.; Roy P.K. (My University, 2025)
The polycrystalline samples of Bi0.9−xSm0.1GdxFeO3 (BSFO) perovskites system, modified with the Gd substitution (0.0 ≤ x ≤ 0.1), were prepared using a solid-state ceramic route. In the present work, the effect of A-site double substitution (Sm and Gd) on Polomska transition before and after solid solubility limit is studied using high-temperature dielectric and conductivity measurements. The X-ray diffraction studies suggest the phase transformation from pure rhombohedral into pseudocubic up to x ≤ 0.05. The lattice parameters are observed to decrease for x ≤ 0.05. After x > 0.05, secondary phases start appearing due to attaining the solubility limit of BiFeO3. The SEM study reveals that the grains are of hexagonal shape and grain sizes are obtained in the range of ∼ 1.9–2.5 µm. The remanent magnetization has observed to increase linearly with the concentration of Gd substitution in BSFO. In the temperature range 80 to 300 °C, the Bi0.825 Sm0.1Gd0.075FeO3 sample (i.e., x = 0.075) follows Arrhenius behavior with almost single slope with significantly enhanced conductivity. This shows that double substitution has suppressed the dielectric anomalies of bismuth ferrite. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.